Advertisements
Advertisements
प्रश्न
`((1 + cosθ + isinθ)/(1 + cosθ - isinθ))^n` = ______.
विकल्प
cos nθ + isin nθ
sin nθ + icos nθ
`cos (nθ)/2 + i sin (nθ)/2`
cos nθ
MCQ
रिक्त स्थान भरें
उत्तर
`((1 + cosθ + isinθ)/(1 + cosθ - isinθ))^n` = cos nθ + i sin nθ.
Explanation:
`(1 + cosθ + isinθ)^n/(1 + cosθ - isinθ)^n`
= `((2cos^2 θ/2 + 2i sin θ/2 cos θ/2)/(2cos^2 θ/2 - 2i sin θ/2 cos θ/2))^n`
= `(cos θ/2 + isin θ/2)^n/(cos θ/2 - isin θ/2)^n`
= `e^(i (nθ)/2)/e^(-(i n-)/2)`
= einθ
= cos nθ + isin nθ
shaalaa.com
क्या इस प्रश्न या उत्तर में कोई त्रुटि है?